Digitalisasi Administrasi Desa Melalui Pelatihan Pengelolaan Data Berbasis Sistem Informasi - Yudhistira Arie Wijaya; Tati Suprapti; Athaullah Abrar Bayan; Beby Maryam (CV. Multi Kreasi Media, 2023)
The rapid development of information technology has encouraged educational institutions and village government institutions to improve the efficiency of administrative services, one of which is in terms of recording attendance. This research aims to develop a QR Code-based attendance system implemented for schools and village institutions as a solution to the manual attendance system that is still vulnerable to fraud and inefficiency. The system development method used is the waterfall method which includes the stages of needs analysis, system design, implementation, testing, and maintenance. This system is designed using PHP programming language and MySQL database, and integrated with QR Code technology that allows users to scan through mobile devices. The test results show that this system is able to record attendance in real-time, generate reports automatically, and improve the accuracy and efficiency of the attendance process. Users also responded positively to the system's simple and easy-to-use interface. With this system, educational institutions and villages can manage attendance data more effectively and transparently. In conclusion, this QR Code-based attendance system is a relevant and applicable innovation in supporting administrative digitization at the local level. This research is expected to be a reference for the development of similar systems in other environments.